1998
DOI: 10.1016/s0735-1097(97)00546-9
|View full text |Cite
|
Sign up to set email alerts
|

Digital Cellular Telephone Interaction With Implantable Cardioverter-Defibrillators

Abstract: We conclude that TDMA-50 cellular telephones did not interfere with these types of ICDs. However, we recommend that the patient not carry or place the digital cellular telephone within 15 cm (6 in.) of the ICD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Over the past 10 years, there have been seven studies that carried out an analysis of interferences on implantable defibrillators due to wireless communication systems. In the study by Fetter et al, 31 the end result was that none of the tests presented oversensitivity problems due to interferences with telephones. Jiménez et al 32 evaluated the interferences caused by GSM 900 MHz with analog and digital mobile and concluded that they had not demonstrated clinically significant EMI and the use of mobile phones seemed to be safe for defibrillator patients.…”
Section: Studies On Emimentioning
confidence: 96%
“…Over the past 10 years, there have been seven studies that carried out an analysis of interferences on implantable defibrillators due to wireless communication systems. In the study by Fetter et al, 31 the end result was that none of the tests presented oversensitivity problems due to interferences with telephones. Jiménez et al 32 evaluated the interferences caused by GSM 900 MHz with analog and digital mobile and concluded that they had not demonstrated clinically significant EMI and the use of mobile phones seemed to be safe for defibrillator patients.…”
Section: Studies On Emimentioning
confidence: 96%
“…In vitro testing indicated that mobile phones could interfere with two ICDs, but during the in vivo phase of the study none of the 41 patients was affected. 4 Large welding machines and electric motors did not interfere with the nor mal functioning of the ICDs tested, 5 although one patient has been described where interference between a washing machine and an ICD resulted in inappro priate shock delivery. 6 Dental equipment has been established as a source of light to moderate electro magnetic fi elds 7 and some devices have been reported to interfere with the activ ity of pacemakers.…”
Section: Introductionmentioning
confidence: 97%
“…Over 100,000 patients received ICDs in 2004 (Hauser, 2005). However, electromagnetic interference from any of several sources can affect the operation of ICDs and the effect of such radiation has been the subject of recent studies (Fetter et al, 1998;Groh et al, 1999;Kolb et al, 2003). To prevent electromagnetic interference from influencing operation, ICDs contain a magnetic reed switch that is closed by a magnetic field (MF) in excess of 10 G (1 G = 100 T) which deactivates the ICD thus rendering the patient without protection from ventricular tachycardia or ventricular fibrillation (Fetter et al, 1996).…”
Section: Introductionmentioning
confidence: 99%